Optical and Electrical Properties of Thermally Treated Hybrid Blend ZnPc/CdS Thin Films - alobaidy, holya a. (Iraqi Journal of Physics, 2019)
Spin coating technique used to prepare ZnPc, CdS and ZnPc/CdS blend thin films, these films annealed at 423K for 1h, 2h and 3h. Optical behavior of these films were examined using UV-Vis. and PL. The absorption spectrum of ZnPc shows a decreasing in absorption with the increase of annealing time while CdS spectrum give a clearly absorption peak at 510 nm. Energy gap of ZnPc increases from 1.41 to 1.52 eV by increasing the annealing time. Eg of CdS decrease by increasing annealing time, from 2.3 eV to 2.2 eV. The intensities of the peaks obtained from PL spectra were strongly dependent on annealing time and confirmed the results obtained from UV-Vis. D.C. conductivity measurement showed that all the thin films have two different activation energies in the temperature range 303–473K.